Deconstructing the Concept of Corporate Social Responsibility: Social Investment on Luwu Indigeous Society - Rahmawati Rahmawati (Journal of Accounting and Investment, 2018)
This research deconstructed the values contained in the concept of Corporate Social Responsibility (CSR) which is used by company for social investment aimed at prospering the community. In fact, consideration on such investment is merely for the profit and reputation of the company. The logos in this research is capitalist which is still the ideology of CSR so that deconstruction is conducted using symbol value of Kedatuan Luwu (Pakka and Payung Ri Luwu). The reality of corporate social responsibility is still on the implementation of handling negative impact caused by company activity. The company operates still with the purpose of maximizing profit which is still filled with material factors based on capitalist ideology. The deconstructed value is the value of profit that is taken into consideration is material in social activities that lead to the concept of capitalism. The intended profit should be the profit that becomes the economic impact of the activity so that the company earns profit and reputation done with dignity before the community and God. The methodology used was qualitative with the paradigm of postmodernism by deconstructing the indigenous symbols of Kedatuan Luwu by including "ade" and "sara" as the order that should be applied in the implementation of CSR to be accepted by local indigenous people. The result of this research was obtained after the researcher deconstructed the concept of CSR proposed by Elkington about Triple Bottom Line (People, Planet and Profit), and analyzing Triyuwono's deconstruction result by adding Prophet and God to CSR concept. From our analysis we found that conflicts between companies and indigenous people were due to the concept of CSR that only emphasized the impact of profit, planet, people, prophet and God were not enough if the way to implement and interact with the local community is still capitalist. Therefore, this study found that its solution is by destroying the logos of capitalism and deconstructing it using the traditional philosophy of Kedatuan Luwu "Pattuppu ri Ade'E Pasanre Ri Sara'E. The philosophy means that whatever conducted in Tana Luwu must be based on the Luwu customs and should not be contrary to the religion.